Pollen production in anemophilous trees - Molina, Rafael Tormo; Rodríguez, Adolfo Muñoz; Palaciso, Inmaculada Silva; López, Francisco Gallardo (Grana, 1996)
Abstract A study was made of the total pollen production per individual tree in ten anemophilous arboreal species (including wild, cultivated and ornamental species) of considerable aerobiological importance: Pinus pinaster, Ulmus minor, Juglans regia, Platanus hispanica, Quercus rotundifolia, Salix atrocinerea, Populus nigra, Acer negundo, Olea europaea and Fraxinus angustifolia. For each species three isolated well-shaped specimens of medium height were chosen, and the number of flowers per individual tree and the number of pollen grains per anther was estimated. The values of total pollen production varied between a little over 1000 million grains in Juglans regia and more than 500,000 million in one single tree in Quercus rotundifolia. For the production of pollen grains per anther, the values oscillated between 3000 grains in Juglans regia and 100,000 in Olea europaea. There is an exponential correlation between the size of the anthers and the number of pollen grains they contain. A linear correlation is also evident between the volume of the tree crown and the total production of inflorescences, flowers, anthers and pollen grains per individual tree. Based on this, a mean coefficient of the number of grains/meter of diameter of the tree crown is obtained which varies between 3.4 ? 108 for Juglans regia and 550.9 ? 108 for Quercus rotundifolia. The ratio between the number of anthers per inflorescence and the number of pollen grains per anther carries out a hyperbolic function; thus, the inflorescences with the most anthers have the anthers with the least pollen and viceversa. This ratio is also manifest between the number of grains per flower and the number of flowers per tree, as well as the number of grains per inflorescence and the number of inflorescences per tree.
doi: 10.1080/00173139609430499doi: 10.1080/00173139609430499The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: anthers; flowers; inflorescences; pollen production; tree crown (voyant)

Pollen production in anemophilous trees (Grana, 1996)
Abstract A study was made of the total pollen production per individual tree in ten anemophilous arboreal species (including wild, cultivated and ornamental species) of considerable aerobiological importance: Pinus pinaster, Ulmus minor, Juglans regia, Platanus hispanica, Quercus rotundifolia, Salix atrocinerea, Populus nigra, Acer negundo, Olea europaea and Fraxinus angustifolia. For each species three isolated well-shaped specimens of medium height were chosen, and the number of flowers per individual tree and the number of pollen grains per anther was estimated. The values of total pollen production varied between a little over 1000 million grains in Juglans regia and more than 500,000 million in one single tree in Quercus rotundifolia. For the production of pollen grains per anther, the values oscillated between 3000 grains in Juglans regia and 100,000 in Olea europaea. There is an exponential correlation between the size of the anthers and the number of pollen grains they contain. A linear correlation is also evident between the volume of the tree crown and the total production of inflorescences, flowers, anthers and pollen grains per individual tree. Based on this, a mean coefficient of the number of grains/meter of diameter of the tree crown is obtained which varies between 3.4 ? 108 for Juglans regia and 550.9 ? 108 for Quercus rotundifolia. The ratio between the number of anthers per inflorescence and the number of pollen grains per anther carries out a hyperbolic function; thus, the inflorescences with the most anthers have the anthers with the least pollen and viceversa. This ratio is also manifest between the number of grains per flower and the number of flowers per tree, as well as the number of grains per inflorescence and the number of inflorescences per tree.
doi: 10.1080/00173139609430499